A 129‐kb Deletion on Chromosome 12 Confers Substantial Protection Against Rheumatoid Arthritis, Implicating the Gene SLC2A3. Issue 2 (2nd December 2013) - Veal, Colin D.; Reekie, Katherine E.; Lorentzen, Johnny C.; Gregersen, Peter K.; Padyukov, Leonid; Brookes, Anthony J.
<x xml:space="preserve">Abstract</x> We describe a copy number variant for which deletion alleles confer a protective affect against Rheumatoid Arthritis. Genotyping in Swedish samples (2403 cases, 1269 controls) revealed a significantly lower frequency of deletion variants in RA cases (p = 0.0012). A similar reduction was seen in UK and US samples, combining the three datasets produces a Mantel–Haenszel OR of 0.497 (p < 0.0002). The deletion spans SLC2A3, a high affinity glucose transporter important in the immune response and chondrocyte metabolism, key aspects of RA pathogenesis <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>